Linear association of the dietary index for gut microbiota with insulin resistance and type 2 diabetes mellitus in U.S. adults: the mediating role of body mass index and inflammatory markers - Qu, Haoran; Yang, Yiyun; Xie, Qihang; Ye, Liu; Shao, Yue (Frontiers in Nutrition, 2025)
BackgroundGut microbiota is reported to be related to the onset of insulin resistance (IR) and type 2 diabetes mellitus (T2DM). The dietary index for gut microbiota (DI-GM) is a novel index for reflecting gut microbiota diversity. We aimed to evaluate the association of DI-GM with T2DM and IR.MethodsThis cross-sectional research comprised 10,600 participants aged ≥20 from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. We employed weighted multivariable linear and logistic regression models to examine the correlation of DI-GM with T2DM and IR. Linear or nonlinear relationships were examined by restricted cubic spline (RCS) regression. Additionally, subgroup and sensitivity analyses were performed to ensure the reliability of the results. Mediation analysis explored the roles of body mass index (BMI) and inflammatory factors in these associations.ResultsHigher DI-GM were inversely associated with T2DM (OR = 0.93, 95%CI: 0.89–0.98) and IR (OR = 0.95, 95%CI: 0.91–0.99) after adjusting for confounders. DI-GM ≥ 6 group showed significantly lower risks of T2DM (OR = 0.74, 95%CI: 0.60–0.91) and IR (OR = 0.77, 95%CI: 0.62–0.95). RCS demonstrated a linear relationship between DI-GM and T2DM, as well as IR. DI-GM was also inversely correlated with the risk markers of T2DM. Mediation analysis showed that BMI and the systemic inflammation response index partly mediated the association of DI-GM with T2DM and IR, while the systemic immune-inflammation index mediated only the association with T2DM.ConclusionDI-GM is inversely associated with T2DM and IR, with BMI and inflammatory markers partly mediating this association.